Assessing the resilience of Kenya's food system: A production approach - Ulimwengu, John M.; Mbuthia, Juneweenex; Omune, Lensa (International Food Policy Research Institute, 2023)
A food system includes all elements (environment, people, inputs, processes, infrastructures, institutions, etc.) and activities that relate to the production, processing, distribution, preparation, and consumption of food, and the outputs of these activities, including socioeconomic and environmental outcomes (HLPE 2017). Thus, a food system links society and nature (Blesh and Wittman 2015). Resilience is “the ability of people, households, communities, countries and systems to mitigate, adapt to, and recover from shocks and stresses in a manner that reduces chronic vulnerability and facilitates inclusive growth” (USAID 2018). Applied to food systems, resilience is defined by the Alliance for a Green Revolution in Africa (AGRA) as the ability to withstand major shocks and stressors emanating from climate/weather, conflict, disease, external economic shocks, and other sources, which, if not prevented or mitigated, would delay, or limit economic progress, transformation, prosperity, and self-reliance (AGRA 2021). In this sense, resilience of a food system may be considered a system property that plays a critical role in its sustainability (Jacobi et al. 2018), thus ensuring sustained food security. This chapter adopts this definition with the objective of assessing the resilience of Kenya’s food system and its components using systemwide metrics. Specifically, we use a production approach based on input–output linkages.